Rise and metabolic roles of Vibrio during the fermentation of crab paste - Xiong, Tian-Han; Shi, Ce; Mu, Chang-Kao; Wang, Chun-Lin; Ye, Yang-Fang (Frontiers in Nutrition, 2023)
Microbial community may systematically promote the development of fermentation process of foods. Traditional fermentation is a spontaneous natural process that determines a unique nutritional characteristic of crab paste of Portunus trituberculatus, However, rare information is available regarding the development pattern and metabolic role of bacterial community during the fermentation of crab paste. Here, using a 16S rRNA gene amplicon sequencing technology, we investigated dynamics of bacterial community and its relationship with metabolites during the fermentation of crab paste. The results showed that bacterial community changed dynamically with the fermentation of crab paste which highlighted by consistently decreased α-diversity and overwhelming dominance of Vibrio at the later days of fermentation. Vibrio had a positive correlation with trimethylamine, hypoxanthine, formate, and alanine while a negative correlation with inosine and adenosine diphosphate. In contrast, most of other bacterial indicators had a reverse correlation with these metabolites. Moreover, Vibrio presented an improved function potential in the formation of the significantly increased metabolites. These findings demonstrate that the inexorable rise of Vibrio not only drives the indicator OTUs turnover in the bacterial community but also has incriminated the quality of crab paste from fresh to perished.